CITRA MEREK PERSEPSI HARGA DAN NILAI PELANGGAN TERHADAP KEPUTUSAN PEMBELIAN PADA MINI MARKET INDOMARET LONTAR SURABAYA - Indriana Kristiawati; Achmad Daengs GS; Ani Herna Sari; Heri Kusyanto (JMM17 : Jurnal Ilmu ekonomi dan manajemen, 2019)
The purpose of this study was to determine the effect of brand image, price perception, and customer value on purchasing decisions both partially and simultaneously on the Indomaret Lontar Surabaya Mini Marke. The sample amounted to 94 respondents with a sampling technique used is purposive sampling. while the method of data analysis used multiple linear regression analysis, validity and reliability tests and using the classic assumption deviation test and hypothesis testing. Based on the test results indicate that the simultaneous F variable brand image, price perception, and customer value has positive and significant impact on purchasing decisions at 50.6% which means that purchasing decisions can be explained by brand image, price perception, and customer value of 50.6 %, and the remaining 49.4% can be explained by other variables. Partially based on t test variables in this study have positive and significant price perception which have the greatest influence in the amount of 32.9%, while the lowest brand image has the effect of 7.3%.Keywords: Brand Image, Perception Price, Customer Value , Purchasing Decisions.